Changes of 5-lipoxygenase pathway and proinflammatory mediators in cerebral cortex and lung tissue of sensitized rats - DENG Yang-mei; XIE Qiang-min; ZHANG Shui-juan; CHEN Ji-qiang; YANG Qiu-huo; BIAN Ru-lian (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
Aim: To explore the change of 5-lipoxygenase (5-LO) pathway expression and proinflammatory mediators level of lung tissue and cerebral cortex, and the possible regulatory mechanism through central nervous 5-LO pathways to pulmonary inflammatory status in antigen repeated challenged rats. Methods: Four groups of rats were treated as control, asthma model, asthma model treatment with dexamethasone (DXM, 0.5 mg/kg, ip) and ketotifen (5 mg/kg, ig). Tumor necrosis factor (TNF)-α, interleukin (IL)-4, interferon (IFN)-γ, and nitric oxide (NO) were detected by ELISA kits. The mRNA expression of 5-LO and LTA4- hydrolase (LTA4-H) was analyzed by reverse transcription-polymerase chain reaction (RT-PCR), and the protein content of 5-LO was measured by Western blot. Results: Increase of TNF-α, IL-4, NO level, and decrease of IFN-γ level in bronchoalveolar lavage fluid (BALF) and cerebral cortex in sensitized rats were shown after repeated antigen challenge. The expression of 5-LO and LTA4-H mRNA, and 5-LO protein levels were increased in lung tissue and cerebral cortex in asthma rats. In comparison with the asthma model, DXM significantly inhibited the increase of cytokine levels and the expression of 5-LO pathway enzyme (P